Romantic Periodicals and Print Culture - Wheatley, Kim (Taylor and Francis, 2012)
Building on a revival of scholarly interest in the cultural effects of early 19th-century periodicals, the essays in this collection treat periodical writing as intrinsically worthy of attention not a mere backdrop to the emergence of British Romanticism but a site in which Romantic ideals were challenged, modified, and developed.Contributors to the volume discuss a range of different periodicals, from the elite Quarterly and Edinburgh Reviews, through William Cobbett's populist weekly newspaper Two-Penny Trash, to the miscellaneous monthly magazines typified by Blackwood's. While some
Keywords: English literature - 18th century - History and criticism; English literature - 19th century - History and criticism; English prose literature--19th century--History and criticism; Gender identity in literature; Periodicals - Great Britain - History - 19th century; Romanticism - Great Britain